Reminiscence and the social relations of ageing: a discourse-analytic study of reminiscence work with older people - Kevin Buchanan (1993)
'Reminiscence work' is currently a popular component of care provision for older people in the UK. However, despite the prevalence of positive 'anecdotal' reports, systematic research has so far failed to show consistent evidence of the benefits of reminiscence work for older people. [Continues.]